A data driven approach to the evaluation of ewe, lamb, flock and farmer factors that influence productivity of UK sheep farms - Lima, Eliana (2020)
In light of current concerns about the environmental and economic sustainability of livestock production, a clear understanding of the best husbandry strategies and drivers of animal productivity is paramount. In the United Kingdom (UK) alone there are 17 million breeding sheep, representing an important share of the total ruminant population; however, there is no baseline information on the most common sheep husbandry practices or which factors make an enterprise most productive. In this context, this thesis aimed at expanding the current knowledge on the most common management strategies implemented by UK sheep farmers, and at comparing the productivity levels across farms, to gain an understanding of the factors and practices related to enterprise production. Since the growth of lambs greatly influences the productivity of a flock, a further objective was to explore in detail the role of disease on lamb growth. Furthermore, because flock recording practices were hypothesised to have a positive influence on productivity, an additional aim of this work was to explore the factors behind adoption of technology on sheep farms for recording of animal information.